Estimation of the mass of microplastics ingested – A pivotal first step towards human health risk assessment - Senathirajah, Kala; Attwood, Simon; Bhagwat, Geetika; Carbery, Maddison; Wilson, Scott; Palanisami, Thava (Journal of hazardous materials, 2021)
The ubiquitous presence of microplastics in the food web has been established. However, the mass of microplastics exposure to humans is not defined, impeding the human health risk assessment. Our objectives were to extract the data from the available evidence on the number and mass of microplastics from various sources, to determine the uncertainties in the existing data, to set future research directions, and derive a global average rate of microplastic ingestion to assist in the development of human health risk assessments and effective management and policy options. To enable the comparison of microplastics exposure across a range of sources, data extraction and standardization was coupled with the adoption of conservative assumptions. Following the analysis of data from fifty-nine publications, an average mass for individual microplastics in the 0–1 mm size range was calculated. Subsequently, we estimated that globally on average, humans may ingest 0.1–5 g of microplastics weekly through various exposure pathways. This was the first attempt to transform microplastic counts into a mass value relevant to human toxicology. The determination of an ingestion rate is fundamental to assess the human health risks of microplastic ingestion. These findings will contribute to future human health risk assessment frameworks. [Display omitted] •Ubiquitous presence of microplastics in the food web.•Microplastics mass ingestion rate is fundamental to assess the human health risk.•This study utilised the existing evidence to determine a global average rate of microplastic ingestion.•The findings of this study will contribute to the human health risk assessment frameworks.